Influenza Surveillance in an Urban Area - W Paul Glezen (Canadian Journal of Infectious Diseases)
In Houston the yearly influenza epidemics have been defined virologically by community surveillance obtained by testing specimens submitted from patients with acute respiratory illnesses seen by sentinel physicians. Mortality attributed to influenza and pneumonia has increased regularly during the period of intense influenza virus activity, but the peak has lagged two weeks behind the peak of activity defined by the virological surveillance. Most of the deaths occurred in persons aged 65 years and older; the average annual rate has been 103.5 per 100,000 in that age group. Hospitalizations for pneumonia and other acute respiratory conditions also peaked during influenza epidemics; the highest rate occurred in the elderly, but children under five years of age also had high rates. Morbidity in the ambulatory setting was highest in children. The average visit rate for children under five years of age was 28%; the rate decreased to about 10% for persons aged 10 years and older. Improved coverage with more immunogenic vaccines is needed to protect the elderly. Young children would benefit from universal immunization with available live attenuated vaccines.